2012
DOI: 10.1038/jid.2011.319
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Risk of Type 2 Diabetes among Women and Men in the United States: A Population-Based Cohort Study

Abstract: Type 2 diabetes (T2D) shares some common risk factors with psoriasis. We evaluated the association between psoriasis and risk of incident T2D among women and men in the United States in a mixed retrospective-prospective cohort study. 184,395 participants were included from an older cohort of women (the Nurses’ Health Study, NHS) (1996–2008), a younger cohort of women (NHS II) (1991–2007) and an older cohort of men (Health Professionals’ Follow-Up Study, HPFS) (1986–2006). During 2,700,958 person-years of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 47 publications
2
48
0
3
Order By: Relevance
“…In particular, psoriasis self-reports have reached a confirmation rate of 92% (22). Furthermore, we compared the characteristics of participants who responded to psoriasis questions with those who did not respond, and found that the main characteristics (e.g., BMI, smoking, and alcohol intake) were similar between responders and non-responders (42). Therefore, it is less likely that our results would differ greatly due to response bias.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, psoriasis self-reports have reached a confirmation rate of 92% (22). Furthermore, we compared the characteristics of participants who responded to psoriasis questions with those who did not respond, and found that the main characteristics (e.g., BMI, smoking, and alcohol intake) were similar between responders and non-responders (42). Therefore, it is less likely that our results would differ greatly due to response bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some data are available regarding the association between psoriasis and individual disease onset risk. Certain studies have reported that psoriasis is associated with a high risk of DM development [18][19][20] , but only few studies have assessed the association of psoriasis with HTN development 21,22 . Nevertheless, most of the studies were cross-sectional in nature and hence lacked a temporal order.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that there is a link between development of psoriasis and diabetes. In fact, recent report has found an association between psoriasis and risk of diabetes in a population-based cohort study [14]. Different studies have suggested that psoriatic patients carry an elevated risk of malignancy although conflicting results have been reported [15][16][17].…”
Section: Introductionmentioning
confidence: 98%